A Solid Fluids Lexicon. (March 2022) - Clark, Nigel; Engelmann, Sasha; Gruppuso, Paolo; Ingold, Tim; Krause, Franz; Lucas, Gavin; Meulemans, Germain; Simonetti, Cristián; Szerszynski, Bronislaw; Watts, Laura
In our discussions around the theme of solid fluids, we often resort to everyday words, many of them of ancient derivation and rich in association. We have decided to make a list of some of the words that come up most often – barring those that already figure as the principal characters of individual contributions – and to distribute among ourselves the task of writing a sort of mini-biography for each. The resulting lexicon with 19 entries, ranging from 'cloud' and 'concrete' to 'wave' and 'wood', serves as a conclusion to the collection as a whole.